Comparison of the improved processes for amyl acetate synthesis by reactive distillation in different operating modes. Issue 6 (3rd November 2019) - Zhang, Qingrui; Liu, Yan; Guo, Tong; Xu, Pengfei; Wang, Yujun
Abstract: The application of heat integrated technology can decrease the energy consumption of the reactive distillation process but also increase the coupling degree, which means that the trouble of control is increased. As the improved process of the conventional reactive distillation (CRD) process with excess reactant feed, the design and control of a reactive dividing‐wall column (RDWC) process are explored for synthesizing amyl acetate. The results indicate that the TAC exhibits 12.15% savings compared with the CRD process and robust control is implemented in control schemes CS2 and CS3. In the analysis of the dynamic response results, a novel analytical method is applied, which includes a comprehensive analysis of the vapour flow rate and conversion rate. In addition, the economics and controllability of the two improved processes for synthesizing amyl acetate are compared that involve the different pressure thermally coupled reactive distillation (DPT‐RD) and RDWC processes. The comparison results indicate that the steady‐state economics of the RDWC process are less than those of the DPT‐RD process, but the RDWC process is more applicable industrially in terms of controllability, in which only the tray temperature control is required.